2002
DOI: 10.1111/j.0014-3820.2002.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Embryo Size in Angiosperms and Other Seed Plants: Implications for the Evolution of Seed Dormancy

Abstract: Seed dormancy plays an important role in germination ecology and seed plant evolution. Morphological seed dormancy is caused by an underdeveloped embryo that must mature prior to germination. It has been suggested that the presence of an underdeveloped embryo is plesiomorphic among seed plants and that parallel directional change in embryo morphology has occurred separately in gymnosperms and in angiosperms. We test these hypotheses using original data on embryo morphology of key basal taxa, a published datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 77 publications
6
125
0
6
Order By: Relevance
“…Several authors have supported the hypothesis that an underdeveloped embryo is an ancestral character among seed plants (Forbis et al, 2002;Verdú , 2006). In accordance with this hypothesis, species of the Ranunculaceae considered basal in the Eudicots, in general have an underdeveloped embryo (Engell, 1995;Martin, 1946).…”
Section: Introductionmentioning
confidence: 76%
“…Several authors have supported the hypothesis that an underdeveloped embryo is an ancestral character among seed plants (Forbis et al, 2002;Verdú , 2006). In accordance with this hypothesis, species of the Ranunculaceae considered basal in the Eudicots, in general have an underdeveloped embryo (Engell, 1995;Martin, 1946).…”
Section: Introductionmentioning
confidence: 76%
“…Morphological dormancy delays germination timing by the time the embryo needs to grow inside the seed before germination can take place (Baskin and Baskin 1998). This type of dormancy was found to occur in most of the ANITA grade (Forbis et al 2002) and may explain the delay of germination observed for A. trichopoda. Germination capacity seems associated with the color change of the exocarp as a germination rate of about 43 % was found for green/red fruits and over 80 % for red fruits.…”
Section: A New Model For Flowering and Fruiting Cyclesmentioning
confidence: 84%
“…The embryo is axillary, inverted foliate ( Figure 4A), i.e., it has large and thick cotyledons that enclose much of the radicle ( Figure 4B). Previous studies have argued that these embryos are more advanced and evolutionarily developed with respect to other types of plant embryos (Forbis, Floyd, & De Queiroz, 2002;Vanderlook, Verdú, & Honnay, 2012), being a beneficial trait in dry habitats (Vanderlook et al, 2012). A developed embryo would be ready to germinate during short periods of humidity in dry forests (Vivrette, 1995), after restrictions caused by the endosperm and coat are eliminated.…”
Section: Variación De Rasgos Morfológicosmentioning
confidence: 99%
“…El embrion es axilar, foliado tipo invertido (Figura 4A), es decir presenta cotiledones grandes y gruesos que encierran gran parte de la radícula (Figura 4B). Estudios previos han argumentado que este tipo de embriones son más avanzados y desarrollados evolutivamente con respecto a otros tipos de embriones vegetales (Forbis, Floyd, & De Queiroz, 2002;Vanderlook, Verdú, & Honnay, 2012), siendo un rasgo beneficioso en hábitats secos (Vanderlook et al, 2012). Un embrión desarrollado estaría listo para germinar durante los periodos cortos de humedad en los bosques secos (Vivrette, 1995), luego que las restricciones provocadas por el endospermo y testa se elimimen.…”
Section: Water Absroption In Seedsunclassified